PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI DINAS PENDIDIKAN, PEMUDA DAN OLAHRAGA DI KABUPATEN KAPUAS HULU - admin, RISA MARRMISYARIATIN B11111009 (Jurnal Manajemen Update, 2016)
Organizational culture, and motivation, the company implemented properly, it will trigger the morale and a positive influence on employee performance improvement results. This study aimed to analyze the influence of organizational culture, and motivation to employee performance at the Department of Education, Youth and Sports Kapuas Hulu. This study uses causal and survey. Total population of the whole 67 staff at the Department of Education, Youth and Sports Kapuas Hulu, while the tested samples were taken of the total population of 67 respondents. Sampling technique used in this study is saturated or census sampling, are all members of the population sampled. The analytical tool used in this research is multiple linear regression analysis. The results showed that organizational culture significant positive effect on employee performance, while motivation is not significant positive effect on the performance of employees at the Department of Education, Youth and Sports Kapuas Hulu. Keywords: organizational culture, motivation and performance of employees.